2007
DOI: 10.1111/j.1365-2648.2007.04396.x
|View full text |Cite
|
Sign up to set email alerts
|

Encounters in Swedish nursing homes: a hermeneutic study of residents’ experiences

Abstract: The insights gained from the study can guide nurses in their encounters with residents in nursing homes so that they feel respected as unique human beings and part of a community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(84 citation statements)
references
References 28 publications
3
81
0
Order By: Relevance
“…In most of the studies, the average ages of the elderly patients and residents included in this literature review was between 78 and 86 years, respectively 20 27 29–32 35 36. One of the inclusion criteria that was often used was that the ‘elderly patient needs to be able to communicate, that he/she needs to have the necessary cognitive and/or physical skills to complete the questionnaire and to answer the questions’ 18 20 27 29–31 33–36.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of the studies, the average ages of the elderly patients and residents included in this literature review was between 78 and 86 years, respectively 20 27 29–32 35 36. One of the inclusion criteria that was often used was that the ‘elderly patient needs to be able to communicate, that he/she needs to have the necessary cognitive and/or physical skills to complete the questionnaire and to answer the questions’ 18 20 27 29–31 33–36.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in the USA,18 28 30 33 34 four in Sweden,20 27 29 36 two in Canada32 35 and one in Australia 31…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting with colleagues on the relationship between existential loneliness and health care could open up discussions of alternative approaches. Westin and Danielson (2007) showed that encounters with nursing home staff influenced older people’s feelings of “being somebody” or “being nobody”. Both residents and professionals effected the encounters, although professionals were responsible for the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Eriksson [13], suffering related to care is an unnecessary suffering that can largely be eliminated if a more humane perspective permeates the healthcare environment. According to Westin and Danielson [41], encounters based on confirmation-that is, seeing, listening to, and understanding others and taking them seriously-will evoke feelings of being valued and respected as unique individuals, which can increase feelings of well-being.…”
Section: Discussionmentioning
confidence: 99%